Incidencia de la incorporación tecnológica de la información y comunicación en la competitividad comercial para América Latina, un análisis econométrico con datos panel, mediante técnicas de cointegración y causalidad, en el periodo 2000-2019 - Jiménez Díaz, Adriana Mishell (2022)
Information and communication technologies play a key role in accelerating the economic and social globalization of countries, taking into account that, despite the fact that their impact has been unequal throughout the world, 430 million people in 2019 are users Internet in Latin America and the Caribbean, being the fourth region with the highest insertion of Internet users (ECLAC, 2021). For this reason, this research is aimed at studying the impact of information and communication technologies on commercial competitiveness, using panel data for thirteen Latin American economies for the period 2000-2019. Through a statistical and econometric analysis and cointegration techniques of Westerlund (2007) and the causality test of Dumitrescu and Hurlin (2012). The results indicate the existence of a negative correlation between information and communication technologies and commercial competitiveness for Latin American countries, but also a long-term relationship and a positive association between the variables. Likewise, bidirectional causality was evidenced between commercial competitiveness and information and communication technologies. Therefore, policies are suggested that allow countries the efficient incorporation of information and communication technologies that give way to a better degree of commercial competitiveness of Latin American countries in addition to the application of technologies in the productive system of companies through training, additionally the creation of networks and synergies between companies, universities and research centers.